AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN SONG LYRICS OF THE ALBUM OF GG BB XX BY LANY - Danisa Salsabila; Ratini Setyowati (Universitas Duta Bangsa Surakarta, 2024)
Sometimes people will face problems understanding the song’s meaning. One of the reasons is caused by the use of Figurative Language. Therefore, this study analyzes about figurative language found in LANY's song lyrics in the